Simulation the Radiation Zone of Al-Mussaib Power Plant by Using Monte Carlo Method - Al-Hattab, Tahseen Ali; Al-Assady, Ali Abd Al-Muhsen; Abd Al-Wahid, Wisam Ahmed (Iraqi Journal of Chemical and Petroleum Engineering, 2015)
The temperature distributions are to be evaluated for the furnace of Al-Mussaib power plant. Monte Carlo simulation procedure is used to evaluate the radiation heat transfer inside the furnace, where the radiative transfer is the most important process occurring there. Weighted sum of gray-gases model is used to evaluate the radiative properties of the non gray gas in the enclosure. The energy balance equations are applied for each gas, and surface zones, and by solving these equations, both the temperature, and the heat flux are found.   Good degree of accuracy has been obtained, when comparing the results obtained by the simulation with the data of the designing company, and the data obtained by the zonal method. In the above work, a code of Monte Carlo method is built, and used to overcome the mathematical analysis.